Forgotten gods: Zalmoxidae of the Philippines and Borneo (Opiliones: Laniatores) - Sharma, Prashant P.; Buenavente, Perry A. C.; Clouse, Ronald M.; Diesmos, Arvin C.; Giribet, Gonzalo (Zootaxa, 2012)
The limits of zalmoxid distribution in Southeast Asia are poorly understood, but a focus of recent research. Here we describesix new species of litter-inhabiting harvestmen in the genus Zalmoxis Sørensen, 1886 (Opiliones: Laniatores: Zalmoxidae)using light microscopy and SEM. Three of these species are from the Philippine Islands (Zalmoxis gebeleizis sp. nov., Zalmoxisderzelas sp. nov., and Zalmoxis sabazios sp. nov.) and the other three from Borneo (Zalmoxis zibelthiurdos sp. nov., Zalmoxisbendis sp. nov., and Zalmoxis kotys sp. nov.). The collecting localities of these species add to the known range of Zalmoxidae,which have not previously been reported from Borneo. The new species add to known morphological variation of Zalmoxis, specifically with respect to sexually dimorphic tarsomeres, body size, and armature of the anal plate.